METHODS, INSTRUCTIONAL TECHNIQUES, AND TEACHING AIDS FOR DEVELOPING ENGLISH DISCOURSE COMPETENCE (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article explores the importance of developing discourse competence in foreign language education for students. In the context of growing international collaboration and the global labor market, medical professionals are expected to communicate effectively in foreign languages. The study distinguishes between the concepts of "competence" and "competency," emphasizing the need for not only knowledge but also practical communication skills. It also defines discourse as a communicative phenomenon that includes both verbal and non-verbal aspects, contextual factors, and cultural appropriateness. Special attention is given to the integration of discourse-based approaches in foreign language instruction, highlighting their effectiveness in training competent medical specialists capable of participating in international academic and professional settings.